2014
DOI: 10.4149/neo_2013_089
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative study of clinicopathological significance, BIRC7, and STC2 expression between squamous cell/adenosquamous carcinomas and adenocarcinoma of gallbladder

Abstract: Gallbladder cancers (GBCs) are uncommon, but highly aggressive cancers. The majority of GBCs are adenocarcinomas (ACs), but rare subtypes of GBCs such as squamous cell carcinoma (SC) and adenosquamous carcinoma (ASC) are observed as well. The clinicopathological characteristics of SC/ASC have not been well documented. Expressions of BIRC7 and STC2 were observed in some tumors. However, BIRC7 and STC2 expressions and clinical significances in gallbladder cancer have not been reported.In this study, the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“… 22 In squamous cell/adenosquamous carcinomas and adenocarcinoma of gallbladder, BIRC7 expression was an independent poor prognostic factor in terms of postoperative survival. 7 Although the oncogenic effects of BIRC7 have been reported in prostate cancer, its prognostic value has not been explored. In fact, current prognostic tools such as clinicopathological parameters lack sufficient accuracy to effectively predict recurrence in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In squamous cell/adenosquamous carcinomas and adenocarcinoma of gallbladder, BIRC7 expression was an independent poor prognostic factor in terms of postoperative survival. 7 Although the oncogenic effects of BIRC7 have been reported in prostate cancer, its prognostic value has not been explored. In fact, current prognostic tools such as clinicopathological parameters lack sufficient accuracy to effectively predict recurrence in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…STC1 was reported to be a Ras-induced gene leading to the aggressive tumor growth of ovarian cancer in vitro and in vivo (14). STC2 overexpression was found to be associated with cancer progression and worse clinical outcome (15)(16)(17)(18). Previous findings showed that STC2 was regulated by HIF-1 under hypoxic conditions and the induction of STC2 stimulated cell proliferation and promoted EMT formation in ovarian cancer (19).…”
Section: Introductionmentioning
confidence: 98%
“…An increasing number of studies have indicated that STC2 is overexpressed in various types of cancer, such as breast cancer, [810] colorectal cancer, [11,12] gastric cancer, [13,14] esophageal cancer, [15] gallbladder cancer, [16] hepatocellular cancer, [17] nasopharyngeal cancer, [18] laryngeal cancer, [19] cervical cancer, [20] ovarian cancer, [21] and endometrial cancer. [22] Besides, high expression of STC2 is significantly associated with poor prognosis in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Besides, high expression of STC2 is significantly associated with poor prognosis in malignant tumors. [1113,16,17,1922] However, Todd et al found that high STC2 expression was prognostic for favorable overall survival (OS) in breast cancer. [9] Therefore, the prognostic value of STC2 expression in solid tumors is controversial.…”
Section: Introductionmentioning
confidence: 99%